Three-dimensionally Ordered Macroporous β-Bi2O3 with Enhanced Electrochemical Performance in a Li-ion Battery. (1st October 2016) - Li, Zhen; Zhang, Wei; Tan, Yueyue; Hu, Jinbo; He, Siyao; Stein, Andreas; Tang, Bohejin
Abstract: This paper describes a modified colloidal crystal templating method to prepare three-dimensionally ordered macroporous (3DOM) β-Bi2 O3 . The 3DOM β-Bi2 O3 materials exhibit higher specific capacities and better capacity retention than conventional β-Bi2 O3 nanoparticles as anode materials for Li-ion batteries. The initial discharge capacity of 3DOM β-Bi2 O3 was as high as 1296 mA h g −1 and the fourth discharge capacity was 526 mA h g −1, whereas the discharge capacity of conventional non-templated β-Bi2 O3 was only 299 mA h g −1 after 4 cycles at a current rate of 0.2C. The improved electrochemical behavior of the 3DOM β-Bi2 O3 electrodes is attributed to the 3DOM architecture, which provides easy access for Li + ions to the surface of active material nanoparticles and short diffusion paths within the macropore walls, and also to the unique tunnel structure of β-Bi2 O3 .